Effect of electroacupuncture on hippocampal protein lactylation in a rat model of vascular dementia - Chen, Yinghua; Sun, Wei; Sun, Zhongren; Zhao, Hongxu; Wu, Tong; Song, Yuanyu; Wang, Haoyu; Qin, Ruiqi; Su, Xiaoqing; Li, Junfeng; Miao, Yue; Li, Xinran; et al. (Frontiers in Neurology, 2025)
BackgroundVascular dementia (VD) is the only preventable form of dementia-related disease. Electroacupuncture (EA) has been shown to provide significant benefits in the treatment of VD. However, the mechanisms through which EA exerts its therapeutic effects remain unclear. Protein lactylation modification (Kla) is a novel type of post-translational modification that has been shown to be involved in various physiological and pathological processes, including inflammation, immunity, and neurodegenerative diseases. This study, utilizing 4D-Fast data-independent acquisition lactylation quantitative proteomics technology, investigated for the first time the effect of EA intervention on protein lactylation in the hippocampal tissue of rats with VD.MethodsRats were randomly assigned to three groups: sham surgery (sham), model [four-vessel occlusion (4-VO)], and EA (4-VO + EA). A rat model of VD was established using the four-vessel occlusion (4-VO) method. The 4-VO + EA group underwent EA intervention at the “Shencong” (Ex-HN01) and “Fengchi” (GB 20) acupoints for 21 consecutive days. After behavioral testing, we collected rat tissues for lactylation modification proteomics analysis.ResultsThe results indicate that EA enhances learning and memory in rats. Based on lactylation modification proteomics analysis, compared to the sham group, 93 lactylation sites on 76 lactylated proteins were upregulated, whereas 29 lactylation sites on 25 lactylated proteins were downregulated in the 4-VO group. Compared to the 4-VO group, 381 lactylation sites on 250 lactylated proteins were upregulated, whereas 18 lactylation sites on 14 lactylated proteins were downregulated in the 4-VO + EA group. Of these, 12 lactylated proteins, including Vdac3 and Pacsin1, exhibited significant differences in lactylation modification levels between the 4-VO and sham groups. The sites of lactylation of these proteins tend to recover after EA intervention. Functional enrichment and clustering analyses revealed that these proteins were primarily associated with pathways, including the nucleotide-binding and oligomerization domain (NOD)-like receptor signaling pathway, and synaptic vesicle cycle. Importantly, we assessed whether the lactylation modification level of Vdac3 was enhanced following EA intervention.ConclusionEA improved cognitive dysfunction in VD rats, and its mechanism may be related to the regulation of protein lactylation modifications in the hippocampal tissue. It involves multiple targets and pathways and may be related to the enhanced level of Vdac3 lactylation modification.